Differential performance regarding the relationship of C3-epi-25(OH)D3 levels and %C3-epi-25(OH)D3 with common pediatric diseases: a case control study - Tao Yang; Xiaohong Chen; Miyan Wang; Shaohua Xu; Dong Hu; Jie Tang; Yuwei Yang (BMC, 2024)
Abstract Background Recently, the C3-epimer of 25-hydroxyvitamin D [C3-epi-25(OH)D] has become a topic of interest among 25-hydroxyvitamin D [25(OH)D] metabolites. Although it can lead to an overestimation of vitamin D storage, its relationship with disease occurrence remains controversial, possibly related to the great extent of tracking of 25(OH)D by C3-epi-25(OH)D over time. This study aimed to investigate the differential performance of C3-epi-25(OH)D3 and its percentage [%C3-epi-25(OH)D3] with respect to 20 common paediatric diseases. Methods This study involved 805 healthy children and adolescents and 2962 patients with common paediatric diseases. We investigated sex, age, and seasonal differences in C3-epi-25(OH)D3 and %C3-epi-25(OH)D3 levels; their variations on 20 common paediatric diseases; and their degree of correlation with 25(OH)D3 levels and various diseases. Results Among the healthy underage participants, C3-epi-25(OH)D3 and %C3-epi-25(OH)D3 changed similarly, with no sex differences. Moreover, their levels were higher in the infant period than in the other periods (t = 5.329-5.833, t = 4.640-5.711, all Padj < 0.001), and in spring and summer than in autumn and winter (t = 3.495-6.061, t = 3.495-5.658, all Padj < 0.01). Under healthy and disease conditions, C3-epi-25(OH)D3 was positively correlated with 25(OH)D3 (ρ = 0.318 ~ 0.678, all P < 0.017), whereas %C3-epi-25(OH)D3 was not, except in patients with nephrotic syndrome (ρ=-0.393, P = 0.001). Before and after adjusting for 25(OH)D3, the relationship of C3-epi-25(OH)D3 with the diseases was notably different. However, it was almost consistent for %C3-epi-25(OH)D3. Our results indicated that %C3-epi-25(OH)D3 was associated with short stature, nephrotic syndrome, lymphocytic leukaemia, rickets, paediatric malnutrition, and hypovitaminosis D (OR = 0.80 ~ 1.21, all P < 0.05). Conclusions The %C3-epi-25(OH)D3 can correct the properties of C3-epi-25(OH)D3 to better track 25(OH)D3 and may be more suitable for exploring its pathological relevance. Further detailed studies of each disease should be conducted.